Relevansi Tata Susila dan Pendidikan Karakter dalam Teks Yakṣa Praśna - I Made Ariasa Giri (Jayapangus Press, 2026)
Character education is widely developed through universal and secular approaches, but noble values can also be drawn from local and religious sources, including teachings from sacred Hindu texts such as the Yakṣa Praśna. Scientific studies linking ethics in Hinduism with national character education are still limited. Therefore, it is important to conduct research that delves into the relevance of moral teachings in Yakṣa Praśna as a source of character education values. The purpose of this research is to understand and describe the values of Hindu ethics relevant to character education, sourced from the Yakṣa Praśna text. This research applies the library research method with a descriptive qualitative approach, referring to the primary data source, namely the Yakṣa Praśna text. The data analysis techniques used in this study are: (1) analyzing the Yakṣa Praśna text, (2) linking moral values with character education, and (3) interpreting the relevance of Hindu moral values in the Yakṣa Praśna to the formation of student character in the modern era. (4) Presenting the findings in a systematic thematic description. The research findings indicate that the Yakṣa Praśna text contains values of religiosity, responsibility, peacefulness, and discipline that align with the principles of character education. These values can serve as a guide for students in forming an ethical and noble personality.